Reconstruction of retroauricolar surgical defect using the "Jigsaw puzzle" advancement flap - Michela Curzio; Vittorio Macchini; Giovanni Di Lella; Antonio Massaro; Giulio Sonego (PAGEPress Publications, 2023)
We present the case of a 55 years old male patient who came to our attention because of a basal cell carcinoma of the right retroauricolar area, near the mastoid-auricle border. The tumour had a size of about 1,5 cm. Repairing retroauricolar surgical defects may be actually very challenging, firstly because an incorrect reconstruction may result in severe deformities which are extremely hard to conceal; so we decided to employ the "jigsaw puzzle" advancement flap, a versatile flap, firstly successfully used in the reconstruction of a nasal ala defect.